1999
DOI: 10.4141/p98-097
|View full text |Cite
|
Sign up to set email alerts
|

Regrowth of crested wheatgrass (Agropyron cristatum [L.] Gaertn.) following defoliation

Abstract: ] Gaertn.) on the amount of time required to reach peak regrowth, the lag period for regrowth to begin, regrowth biomass, tiller survival and replacement, and carryover effects of defoliation the following year were investigated. Regrowth of crested wheatgrass was determined during the summers of 1990, 1991 and 1992 in central Saskatchewan following a single defoliation to a 5-cm stubble height at eight stages of growth. Crested wheatgrass regrew 54-130 g m -2 of biomass when defoliated tillers had ≤3.6 leaves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Since crested wheatgrass disperses only by seed, controlling seed production will slow invasion. Defoliation is not adequate for complete control (Romo and Harrison 1999). However, defoliation is likely more efficient at controlling crested wheatgrass than are herbicides (Wilson and Pärtel 2003;Hansen and Wilson 2006).…”
Section: Restoration and Managementmentioning
confidence: 99%
“…Since crested wheatgrass disperses only by seed, controlling seed production will slow invasion. Defoliation is not adequate for complete control (Romo and Harrison 1999). However, defoliation is likely more efficient at controlling crested wheatgrass than are herbicides (Wilson and Pärtel 2003;Hansen and Wilson 2006).…”
Section: Restoration and Managementmentioning
confidence: 99%
“…Matches and Burns (1995) indicated that successful stockpiling of both cool-season grasses and alfalfa for late season utilization required a significant rest period without cutting or grazing. Various studies have utilized resting to prevent overgrazing (Romo 2006), reduce fertilizer application and associated soil acidity (Dorrough et al 2004), increase biomass (Dowling et al 1996) and facilitate plant recovery (Romo and Harrison 1999).…”
mentioning
confidence: 99%
“…This suggests that H. comata was able to offset growing season declines in tiller number under frequent defoliation with greater tiller recruitment between years. Romo and Harrison () observed a similar response in Agropyron cristatum , in which defoliation did not increase tiller populations until the following spring. It is also possible that intensively defoliated tillers avoided senescence prior to the end of the growing season and maintained meristem (i.e., basal bud) viability into the following growing season.…”
Section: Discussionmentioning
confidence: 74%